A 3-D Integrated Common Mode Filter Based on Through Silicon vias Technology. Issue 1 (1st November 2022) - Wang, Fengjuan; Huang, Haoxiang; Yin, Xiangkun; Yu, Ningmei; Yang, Yuan
Abstract : Common mode filters (CMF) are widely used to ensure signal integrity. However, due to the large area, traditional CMFs cannot meet the eager demand for the miniaturization of modern communication systems. In this paper, a three-dimensional integrated CMF based on through silicon vias (TSV) technology is proposed. The adoption of TSV technology greatly reduces the area of CMF. The structure is modeled and simulated by HFSS software. The stopband of the common mode signal is 7.9 GHz ~ 18.8 GHz. In the operating frequency band, the effect of group delay jitter on frequency is less than 10 ps. Moreover, the plane area of the CMF is only 0.195 mm 2 .